(untitled) (Experimental biology, 2016)
Anemia is associated with impaired physical development and cognitive abilities of children , the deterioration of mental and physical activity in adults, increased risk of infectious diseases and a number of other problems. Anemia is characterized by a decrease in red blood cell count and hemoglobin concentration in the blood, the manifestation of iron deficiency, folic acid, vitamin B12 and a number of other nutrients. Among women with anemia were significantly more common adverse pregnancy outcomes than women without anemia . In this context , the aim of our work was to increase the effectiveness of programs to prevent micronutrient deficiencies through the organization of a permanent biological monitoring for security sentinel populations iron, folic acid Zhambyl, Mangistau and Almaty regions.